Element-resolved local lattice distortion in complex concentrated alloys: An observable signature of electronic effects. (1st September 2021) - Oh, Hyun Seok; Odbadrakh, Khorgolkhuu; Ikeda, Yuji; Mu, Sai; Körmann, Fritz; Sun, Cheng-Jun; Ahn, Heh Sang; Yoon, Kook Noh; Ma, Duancheng; Tasan, Cemal Cem; Egami, Takeshi; Park, Eun Soo
Abstract: Complex concentrated alloys (CCAs) are of growing interest due to their outstanding mechanical properties that exceed the property limits of conventional alloys. Whereas the superior properties are often attributed to severe lattice distortion, to date it is not clear what controls the lattice distortion and how it affects the mechanical properties of CCAs. In this work, we study the element-resolved local lattice distortion (ELLD) in CCAs of 3d transition-metal elements (3d CCAs) by the extended X-ray absorption fine structure experiment and the density-functional theory calculations. We show that ELLD is primarily dependent upon charge transfer among elements and affects the properties through atomic-level pressure and orbital transition. The ELLD provides a qualitative measure of the effective atomic size for explaining element-specific properties and macroscopic properties. Graphical abstract: Image, graphical abstract